Factors Affecting Income of Rice Farmers in Tapalang District, Mamuju Regency: Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Padi Di Kecamatan Tapalang Kabupaten Mamuju - Yudiarsyah; H. Herman; Ernawaty Mappigau (Jurnal Actual Organization Of Economic, 2023)
The purpose of this study was to identify and analyze the factors that affect the income of rice farmers in Tapalang sub-district, Mamuju district. This type of research is a quantitative study with a sample of 96 people. Collecting data using literature study techniques, observations, interviews, questionnaires and documentation. The data analysis technique used is multiple linear regression analysis. This research was conducted in January-February 2023. Based on the results of the research and analysis conducted by the researchers, it was concluded that capital, land area, labor and prices partially and significantly affected farmers' income with a tcount value greater than the respective ttable (5.664 > 1.662); (5.302 > 1.662); (3.700 > 1.662) and (4.571 > 1.662 ). Likewise simultaneously which shows that capital, land area, labor and prices have a significant simultaneous effect on farmers' income in Tapalang District, Mamuju Regency with a value of 208.838 > 2.47, which means that fcount is greater than ftable.